The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1093/nar/gkab451
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-dependent inhibition of cGAS and TLR9 DNA sensing by 2′-O-methyl gapmer oligonucleotides

Abstract: Oligonucleotide-based therapeutics have the capacity to engage with nucleic acid immune sensors to activate or block their response, but a detailed understanding of these immunomodulatory effects is currently lacking. We recently showed that 2′-O-methyl (2′OMe) gapmer antisense oligonucleotides (ASOs) exhibited sequence-dependent inhibition of sensing by the RNA sensor Toll-Like Receptor (TLR) 7. Here we discovered that 2′OMe ASOs can also display sequence-dependent inhibitory effects on two major sensors of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…Interestingly, a few ASOs can enhance cGAS sensing when used at low concentrations. The binding of these ASOs to the third DNA binding domain within cGAS was speculated to facilitate the formation of the cGAS oligomer and thus increases its enzymatic activity (70,71). These works suggest that RNA may compete for cGAS binding to dsDNA and inhibit cGAS activity, which has also been confirmed by a preprint study (25).…”
Section: Cgas Could Bind Rna and Recognize Dna-rna Hybridsmentioning
confidence: 66%
See 3 more Smart Citations
“…Interestingly, a few ASOs can enhance cGAS sensing when used at low concentrations. The binding of these ASOs to the third DNA binding domain within cGAS was speculated to facilitate the formation of the cGAS oligomer and thus increases its enzymatic activity (70,71). These works suggest that RNA may compete for cGAS binding to dsDNA and inhibit cGAS activity, which has also been confirmed by a preprint study (25).…”
Section: Cgas Could Bind Rna and Recognize Dna-rna Hybridsmentioning
confidence: 66%
“…As mentioned earlier in the article, cGAS binds to DNA in a sequence-independent manner, which is mainly associated with the length and structures of DNA (21). However, for RNA, it is clear that short synthetic oligos can compete with DNA to bind cGAS in a sequence-dependent manner (70,79), suggesting that it is the sequence rather than the length of the RNA that may be important for the DNA binding activity of cGAS. In summary, a series of RNAs, such as synthetic oligos (70), tRNA (25), and circRNA (22), which all belong to ssRNA, can bind to cGAS and regulate its activity, whereas dsRNA can bind cGAS but does not affect the activity of cGAS (21).…”
Section: Cgas Could Bind Rna and Recognize Dna-rna Hybridsmentioning
confidence: 85%
See 2 more Smart Citations
“…Conversely, ERK1/2 inhibition with SCH772984 strongly limited the expansion of MG-63 and TC-1 cells, and modestly impacted that of HOS cells ( Figures 4A,B ). Having previously shown that MG-63 had a functional cGAS-STING response ( Valentin et al, 2021 ), we reasoned that H151 may block canonical STING signaling basally engaged in these cells, normally restraining their growth. Accordingly, the basal expression of several ISGs ( RSAD2 , IFIT1 , IFIT2 , IFIT3 ) was significantly decreased by H151 treatment in MG-63 cells ( Figure 4D ).…”
Section: Resultsmentioning
confidence: 99%